EVALUASI PEMECAH GELOMBANG PANTAI MANGGAR BARU - Devedo, Mochamad Gaharu Dida; Ismail, Ardhan (Journal of Sustainable Transformation, 2025)
The coastal protection structure in the form of an offshore breakwater has been constructed at Manggar Baru Beach by the local government to address the ongoing issue of coastal erosion. However, despite its construction, several problems remain unresolved. This study aims to evaluate the performance of the constructed breakwater and provide recommendations for alternative, more effective coastal protection designs. The research involves assessing the performance of the breakwater structure and designing alternative coastal protection solutions. The data used in this study consists of secondary data obtained from the East Kalimantan Public Works Department. The evaluation results reveal that in areas near the river mouth, waves are still able to pass through the breakwater structure. Additionally, the river flow, which bends towards the area between the beach and the breakwater, allows water to enter without sufficient protective structures to block it. This indicates that the existing breakwater is not fully effective. As a solution, the proposed coastal protection concept involves extending the length and increasing the height of the breakwater structure. The breakwater is planned to be a rubble structure with the following specifications: crest elevation of +5.5 m LLWL, a total length of 136 m, primary armor layer consisting of tetrapods and crushed stones, and a crest width of 3.2 m.